Extenuation in the Penal Code 2015 and Current Issues - Quynh, Tran Thi (VNU Journal of Science: Legal Studies; Vol 36 No 2, 2020)
Extenuation is considered by the Court when issuing a sentence, manifesting the state’s leniency policy and the classification principle of penal liability in the Penal Code of Vietnam, ensuring efficiency and meaning of penalties. On this basis, this Article provides a new scientific approach to the definition of extenuation, analysing contents and levels of extenuation in provisions of the Penal Code 2015 (revised in 2017), examining issues in practical adjudication, and making recommendations on crime prevention and improvement of rehabilitation and re-education of individual and corporate offenders in the current context of the country. Keywords: extenuation, leniency policy, classification principle, goodness, penalty. References:  [1] National Assembly, Penal Code 2015. [2] Political Bureau, Resolution No. 49-NQ/TW on 2 June 2005 on“Judicial Reform Strategy until 2020”, Hanoi. [3] Supreme People’s Court, Collection of criminal laws, Volume I (1945-1974), Hanoi, 1975. [4] Supreme People’s Court, Collection of criminal laws, Volume II (1974-1978), Hanoi, 1979. [5] National Assembly, Penal Code 1985. [6] National Assembly, Penal Code 1999, revised in 2009. [7] Le Cam, Trinh Tien Viet, Offender’s record: Some basic theoretical issues, People’s Court Journal, Issue No. 1/2002. [8] Trinh Tien Viet, Impact of extenuating circumstances in deciding criminal penalties, Legal Science Journal, Issue No. 1/2004. [9] Justice Council of the Supreme People’s Court, Resolution No. 02/2018/NQ-HĐTP on 15 May 2018 on “Guidance on application of Article 65 of the Penal Code on suspended sentence”. [10] Thieu Van Thinh, Cao Bang People’s Procuracy, https://tapchitoaan.vn/bai-viet/phap-luat/mot-so-luu-y-khi-quyet-dinh-ap-dung-hinh-phat-duoi-muc-thap-nhat-cua-khung-hinh-phat, accessed on 05 May 2020. [11] Justice Council of the Supreme People’s Court, Resolution No. 01/2018/NQ-HĐTP on 24 April 2018 on “Guidance on application of Article 66 and Article 106 of the Penal Code on conditional parole”. [12] Tran Thi Quang Vinh, Extenuating circumstances in Vietnamese criminal law, Doctoral Thesis in Law, Institute of State and Law, Hanoi, 2002. [13] Dao Tri Uc, Vietnam Criminal Law, Volume I –General part, Social Science Publishing House, Hanoi, 2000.